Conceptual Study on Ashmari w.s.r. to Urolithiasis (AYUSHDHARA, 2024)
Ashmari is one of the most common diseases of Mutravaha srotas (urinary system) which occur due to improper functioning of the filtration in the kidney. Acharya Susruta considered Ashmari as a grave disease and fatal as death itself (Astamahagad). Due to food and life style variations, it has become a global problem varying its incidence as per geographical distribution, sex and age group. It is highly prevalent disease with high recurrence rate. Despite the wide range of conservative treatment options, untreated or poorly treated, urolithiasis could result in urinary tract infection, urinary obstruction, chronic kidney diseases, end-stage renal failure and hypertension etc. This article reviews the Ayurvedic concept of Ashmari regarding its classification, symptomatology, etiological factors as well as its contemporary science.